IDEOLOGICAL RESILIENCE MAP OF AL IRSYAD SCHOOL IN INDONESIA - Subando, Joko; Fatimah, Meti; Sukari, S; Baidan, Nashrudin; Alhasbi, Faruq (Proceeding of International Conference of Islamic Education, 2024)
This research aims to obtain a map of the ideological resilience of Al-Irsyad school in Indonesia. This research is survey research conducted in 9 cities involving 806 respondents consisting of Karawang (78 students), Bandung (66 students), Cirebon, (56 students), Purwokerto (214 students), Pemalang (114 students), Surakarta (56 students), Karanganyar (34 students), Bondowoso (68 students) and Banyuwangi (123 students). The instrument for collecting data was the ideological resilience index of Al-Irsyad having guaranteed validity and reliability, and then the collected data were analyzed descriptively quantitatively. The results of this research indicate that Tauhid, Akhlak, and Ukhuwah are the strongest ideological aspects, while knowledge and modernity are the weakest ideological aspects. The strength of the tauhid aspect reveals that the Al-Irsyad school as an ideological agent to purify aqidah and cleanse society from superstition, bida’h, and khurafat is still carrying out its functions properly. The strength of several ideological aspects at SMP Al-Irsyad Al-Islamiyyah Purwokerto recommends the school as a model for internalization and dissemination of ideology for other Al-Irsyad schools.